Experimental and analytical study of bio-based epoxy composite materials for strengthening reinforced concrete structures - Assih Jules (De Gruyter, 2021)
This paper presents a new approach to strengthen reinforced concrete structures using natural fiber composites. Natural fibers are often used in civil engineering for thermal or acoustic insulation, but rarely are they employed to strengthen structures. Natural fiber composites are constituted of a matrix based on epoxy adhesive and aligned continuous fiber reinforcements. In this study, we investigate several fibers (carbon, hemp, fiberglass, and linen) in tensile and bending tests. The bending results show twice the magnification of the ultimate bending load in a strengthened specimen. The study also evaluates the stress distribution in the structure. In the case of a beam strengthened by a bonded carbon plate, the functioning of an assembly single lap and the optimal anchor length was determined by analogy. The analytical study describes the shear and peel stresses in the adhesive, composite, and concrete joints, revealing the optimum values of shear stress near the ends of the adhesive joint. The same was observed in concrete. The tests showed the influence of strengthening on the ultimate load and stiffness as well as the concentration of shear stresses at the ends of the adhesive joint.